Beyonders; Seeds of rebellion / 2. - Mull, Brandon, 1974- (Beyonders, 2013)
After Jason succeeds in finding a way back to Lyrian, he's immediately in more danger than ever. Meanwhile, Rachel and the others have made their own progress--as well as discovered new enemies. As the group ultimately rejoins, they strive to convince their most needed ally to join the war and form a rebellion strong enough to triumph against the emperor.